Revealing Legal Politics in City Branding: A Study of Padang Panjang City as the Kota Serambi Mekah - Abrar, Abrar; Khalida, Azhariah; Hareem, Haya (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to analyze in depth the political power of legal aspects of the branding of the city of Padang Panjang as the Kota Serambi Mekah. The focus of this research explains the reasons behind the branding of the city of Padang Panjang as the City of Serambi Mekkah at the beginning of its determination, the political power of legal (regulations and programs) in building and maintaining the city’s branding. This research uses a qualitative approach. The data sources collected are a combination of data on the law in the books with the law in practices. The interpretation of the data refers to the normative legal research procedure by confirming it to the understanding practices of the respondents. Data was collected through interviews with the mayor and his staff, and the community. While the literature study collected policy documents and the internet such as the Padang Panjang Government website. The empirical approach analyzes field data to explain Padang Panjang’s branding policy as the City of Serambi Mekah, while the normative approach analyzes scientific documents to explain regulations related to the branding. The results of this study show that the rationale behind city branding is to strengthen the Islamic and cultural identity of Padang Panjang City. In addition, although the Kota Serambi Mekah branding has been practically implemented through various regulations and programs, the consistency in the emphasis of branding in strategic planning has changed, from an emphasis on concrete implementation in the 2005-2045 Regional Long-Term Development Plan (RPJPD) to a more explicit emphasis in the Draft RPJPD 2025-2045. This research is novel in exploring the political power of legal in shaping and sustaining the branding of cities, particularly Padang Panjang as the Kota Serambi Mekah. The contribution of this research lies in an in-depth understanding of the role of legal and policy frameworks in strengthening the city’s cultural and religious identity, as well as how this branding can adapt to changes in long-term development strategies. This research also provides suggestions for the government to be consistent in maintaining the implementation of branding in every strategic planning, so that the identity of Kota Serambi Mekah remains relevant and effective in facing social and political challenges.